Measuring Procyclicality Behavior on Islamic and Conventional Banks in Indonesia - Dimas Bagus Wiranatakusuma; Ecky Imamul Muttaqin (Faculty of Economic and Business, 2024)
Research Originality: This study contributes to capturing credit cycle movements during the COVID-19 pandemic and compares sizes of credit and business cycles to promote banking stability.Research Objectives: This study attempts to examine banking behavior on amplitude and frequency indicators by focusing on the credit property of Islamic and conventional banks from 2014 to 2020.Research Methods: Ordinary Least Square, frequency base filter and turning point analysis are used.Empirical Results: This study unveiled that the size of an Islamic bank’s amplitude was higher than conventional bank’s amplitude. Meanwhile, the size of the frequency of Islamic banks had a longer frequency than conventional banks, given Islamic banks rely on real sector-based financing which has a longer period of economic expansion.Implications: It is also argued that conventional banks have a riskier leverage indicated by a higher percentage of amplitude. Thus, it is recommended to Indonesian banking sectors to promote the growth of Islamic banks to achieve financial stability. This research is significance in showing the Islamic banking’s contribution on stability given Indonesia is taking serious effort becoming the epicentrum of Islamic finance growth in the world.JEL Classification: E51, G01, G21How to Cite:Wiranatakusuma, D. B., & Muttaqin, E. I. (2024). Measuring Procyclicality Behavior on Islamic and Conventional Banks in Indonesia. Etikonomi, 23(1), 249 – 270. https://doi.org/10.15408/etk.v23i1.35293.